PENGGUNAAN GAYA BAHASA PEMBANDINGAN DALAM KUMPULAN CERPEN 100 TAHUN CERPEN RIAU - Anshori Ramadhan; Hermandra Hermandra; Elvrin Septyanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study illustrates the use of comparative leanguage style in a anthology of short story books 100 Tahun Cerpen Riau from the perspective of Purwandari. The data source for this study is 10 out of 100 short stories published in the anthology of short story books 100 Tahun Cerpen Riau. This research is qualitative research, not quantitative or numerical. Descriptive methods were used in this study. The steps begin by collecting data, classification, analysis and inference to get a general description of the attractions to be obtained. The data collection technique used in this study is the literature review. Based on the results of data analysis, found the benchmark styles used in the anthology of short story books 100 Tahun Cerpen Riau are 14 allegory data, 4 litotes data, 36 metaphorical data, 16 personification data, 20 simile data, 15 symbolic data, and 15 tropen data. Language styles expressed by the author to comparing words or changes with other expressions that have the same meaning as the author. Using a benchmarking language style to regulate imaginative impressions, the effect of deep meaning, the beauty of diction, concentrated meaning, shorten and improve language, and enhance the estetic of literary works.Key Words: Style of Leanguage, Benchmarks Leanguage Style, Anthology Of Short Story 100 Tahun Cerpen Riau